The (I/Y)XGG motif of adenovirus DNA polymerase affects template DNA binding and the transition from initiation to elongation - Brenkman, A B; Heideman, M R; Truniger, V; Salas, M; van der Vliet, P C (The Journal of biological chemistry, 2001)
Adenovirus DNA polymerase (Ad pol) is a eukaryotic-type DNA polymerase involved in the catalysis of protein-primed initiation as well as DNA polymerization. The functional significance of the (I/Y)XGG motif, highly conserved among eukaryotic-type DNA polymerases, was analyzed in Ad pol by site-directed mutagenesis of four conserved amino acids. All mutant polymerases could bind primer-template DNA efficiently but were impaired in binding duplex DNA. Three mutant polymerases required higher nucleotide concentrations for effective polymerization and showed higher exonuclease activity on double-stranded DNA. These observations suggest a local destabilization of DNA substrate at the polymerase active site. In agreement with this, the mutant polymerases showed reduced initiation activity and increased K(m)(app) for the initiating nucleotide, dCMP. Interestingly, one mutant polymerase, while capable of elongating on the primer-template DNA, failed to elongate after protein priming. Further investigation of this mutant polymerase showed that polymerization activity decreased after each polymerization step and ceased completely after formation of the precursor terminal protein-trinucleotide (pTP-CAT) initiation intermediate. Our results suggest that residues in the conserved motif (I/Y)XGG in Ad pol are involved in binding the template strand in the polymerase active site and play an important role in the transition from initiation to elongation.